A Survey on Dynamic Load Balancing Strategies for A Distributed Computer System (International Journal of Engineering and Computer Science, 2014)
A distributed system consists of independent workstations connected usually by a local area network. The IT infrastructure is playing an increasingly important role in the success of a business. Market share, customer satisfaction and company image are all intertwined with the consistent availability of a company’s web site. Network servers are now frequently used to host ERP, e-commerce and a myriad of other applications. The foundation of these sites, the e-business infrastructure is expected to provide high performance, high availability, secure and scalable solutions to support all applications at all times. However, the availability of these applications is often threatened by network overloads as well as server and application failures. Resource utilization is often out of balance, resulting in the low-performance resources being overloaded with requests while the high-performance resources remain idle. Server load balancing is a widely adopted solution to performance and availability problems. This paper describes a survey on dynamic load balancing strategies for a distributed environment.